Effect of chemical reaction on MHD flow with heat and mass transfer past a vertical porousplate in the presence of viscous dissipation - Satyabrat Kar; N. Senapati; B. K. Swain (Institute of Advanced Engineering and Science, 2019)
An attempt is made to study an unsteady MHD free convective flow with heat and mass transfer past a semi-infinite vertical porous plate immersed in a porous medium. Presence of viscous dissipation and chemical reaction are taken into account. It is assumed that the plate is moved with uniform velocity in the direction of fluid flow. Viscous dissipation term leads nonlinearity in the governing equations. Applying perturbation technique, the solutions for velocity, temperature and concentration are obtained. The effect of various parameters such as Rc, Gr, Gc, Sc etc. on velocity, temperature and concentration are shown through graphs.